Analysis of the Cell Type-Dependence on the Arenavirus Z-Mediated Virus-Like Particle Production - Mpingabo, Patrick I.; Urata, Shuzo; Yasuda, Jiro (Frontiers in Microbiology, 2020)
The arenavirus Z protein facilitates production of virus-like particles (VLPs) through the late (L)-domain, which is located at its C-terminus. In this study, we first examined the efficiency of VLP production by solely expressing Z protein from several different arenaviruses. In addition, we analyzed the role of the L-domains of these arenaviruses’ Z protein among different cell lines in VLP production. VLP assay was performed by transfection of the expression plasmids for Junín virus (JUNV), Machupo virus (MACV), Tacaribe virus (TCRV), Latino virus (LATV), Pichinde virus (PICV), and Lassa virus (LASV) Z proteins into six different cell lines HEK293T, Huh-7, A549, Vero76, BHK-21, and NIH3T3 cells. JUNV, MACV, and LASV Z proteins efficiently produced VLPs in all tested cell lines, while the efficiencies of VLP production by the other arenavirus Z proteins were cell type-dependent. The contribution of the L-domain(s) within Z protein to VLP production also depended on the cell type. These results suggested that each arenavirus has its own particle-production mechanism, which is different among the cell types.